A nonlinear relationship between visceral adipose tissue and frailty in adult lung transplant candidates. Issue 11 (24th July 2019) - Anderson, Michaela R.; Kolaitis, Nicholas A.; Gao, Ying; Kukreja, Jasleen; Greenland, John; Hays, Steven; Wolters, Paul; Golden, Jeff; Diamond, Joshua; Palmer, Scott; Arcasoy, Selim; Udupa, Jayaram; et al.
Abstract : Frailty is a state of decreased physiologic reserve associated with poor outcomes before and after lung transplantation. Obesity, particularly central obesity characterized by excess proinflammatory visceral adipose tissue (VAT), is associated with incident frailty in middle‐aged and older adults. The association between VAT and frailty in advanced lung disease, however, is unknown. In two, nonoverlapping multicenter cohorts of adults listed for lung transplantation, we measured VAT area on bioelectrical impedance assay (BIA) in one cohort and cross‐sectional VAT and subcutaneous adipose tissue (SAT) areas on abdominal computed tomography (CT) in the other. We identified a nonlinear relationship between greater VAT by BIA and frailty. In fully adjusted piecewise regression models, every 20 cm 2 increase in VAT area was associated with 50% increased odds of frailty in subjects with high VAT (95% CI 1.2‐1.9, P  < .001), and 10% decreased odds of frailty (95% CI 0.7‐1.04, P  = .12) in subjects with low VAT. Compared to frail subjects with low VAT, those with high VAT were more likely to have low grip strength and less likely to have weight loss, suggesting that mechanisms of frailty may differ by VAT. Further investigation of mechanisms linking VAT and frailty may identify new targets for prevention and treatment. Abstract : Greater abdominal visceral adipose tissue, as measured by bioelectrical impedance assay or abdominal CT scan, is associated with an increased risk of frailty in a multicenter study of adults listed for lung transplantation.